Evaluasi Implementasi SLiMS dalam Digitalisasi Data Bibliografi dan Layanan Penelusuran Informasi: Studi Kasus di Perpustakaan Politeknik Industri Furnitur dan Pengolahan Kayu - Vivin Agustina; Nukhbah Sany (Universitas Sebelas Maret Library, 2026)
This study aims to evaluate the implementation of the Senayan Library Management System (SLiMS) in bibliographic data digitization to enhance information retrieval services at the Library of the Polytechnic of Furniture Industry and Wood Processing. The research employed a descriptive qualitative approach, with data collected through interviews, observation of Online Public Access Catalog (OPAC) usage, and documentation. Informants consisted of library staff and students as primary users. The findings indicate that implementing SLiMS improves the effectiveness of information retrieval compared to the previous manual system, as reflected in easier online access to collections, faster retrieval times, and users’ independence in locating materials. The OPAC enables users to search by title, author, and subject quickly and accurately. However, several challenges remain, including interface design, mobile compatibility, and the completeness of bibliographic metadata, all of which affect the user experience. The implementation also contributes to more efficient collection management and improved library service quality. This study recommends optimizing the user interface, enhancing bibliographic metadata, and strengthening staff competencies to ensure the sustainability of automated library services